Contextualization in the Faith Refreshment Service at the GMIM Syaloom Karombasan Congregation, South Manado Region One - Rumangu, Christalia Deventi; Tamaweol, Roy Dekky (Proskuneo: Journal of Theology, 2025)
Faith refreshment service is a very important form of worship for the congregation of GMIM Syaloom Karombasan, Manado Selatan Satu Region. This study aims to contextualize the faith refreshment service in the social, cultural, and spiritual aspects of the local congregation. A contextualization approach is needed so that worship is not only limited to rituals, but also relevant to the challenges and needs of the congregation amidst changing times. The method used is qualitative with a descriptive-analytical approach, including in-depth interviews with church servants and congregation members. The results of the study indicate that the contextualization of the faith refreshment service at GMIM Syaloom Karombasan includes adjusting the language, music, and sermon material to be closer to the reality of the congregation's life, but still based on a solid theological foundation. The discussion also reveals that this approach is able to increase the active participation of the congregation and strengthen their faith in facing the challenges of everyday life. However, challenges remain, such as maintaining a balance between tradition and innovation. The conclusion of this study shows that the contextualization of the faith refreshment service is very important in making worship more meaningful and applicable for the congregation of GMIM Syaloom Karombasan.